Pendapatan Nasional 3 Sektor Dan 4 Sektor - Chesia Afriza; Mar’atus Solekhah; Rizky Fadhilah Ahmad; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract: National income is one of the key indicators in measuring the economic welfare of a country, which describes the total value of all goods and services produced in a certain time period. This concept is the basis for understanding the economic dynamics of a country, which reflects production, distribution and expenditure activities in the economy. In national income analysis, the three-sector and four-sector approaches offer different points of view in understanding the structure and interaction of economic sectors. The three-sector approach separates the economy into household, business, and government sectors. Households act as the main consumers influencing aggregate demand, while businesses are responsible for the production of goods and services, and the government has a role in regulating and managing economic activities. On the other hand, the four-sector approach broadens the analysis by including the foreign trade sector, which makes it possible to understand the influence of international trade on national income. In this article, we provide an in-depth discussion of national income in both analytical frameworks, discussing the role of each sector in the formation of national income and its impact on the economy as a whole. We also explore relevant policy implications in the context of the three-sector and four-sector approaches, including strategies to increase economic growth, reduce inequality, and promote societal well-being.